The impact of teacher preparation on preservice teachers' attitudes toward inclusive education in Qatar - Elsayed E.A. Hassanein (Heliyon, 2021)
Teachers' beliefs and attitudes are a significant component in the development and success of inclusive education. Research indicates that the foundation of positive attitudes toward inclusive education can be established in preservice-teacher-preparation programs. This study examines the change in preservice teachers' attitudes toward inclusive education following an inclusion-centered course, combined with an 18-hr practicum. Using the Multidimensional Attitudes toward Inclusive Education Scale (MATIES), 98 preservice teachers from primary and secondary teacher education programs in the College of Education at Qatar University in Doha, Qatar, were surveyed pre and post-course. It was found that all the participants' attitudes toward inclusive education changed significantly. No significant differences between primary and secondary preservice teachers were found at the end of the course. The results illustrated that combining information-based instruction with structured fieldwork experiences can potentially change preservice teachers' attitudes toward inclusive education. Implications for practice and future directions in research are considered.